Analisis Konten Edukasi NPD (Narcisstic Personality Disorder) di Instagram @anti.manipulasi - Dian Indira Putri Sibarani; Muhammad Iqbal (Badan Penerbit STIEPARI Press, 2025)
Instagram has become a significant source of information, including in the field of mental health. The @anti.manipulasi account consistently shares educational content about Narcissistic Personality Disorder (NPD), helping raise public awareness—especially for individuals affected by NPD—while demonstrating the role of technology in supporting mental health understanding. This study aims to analyze how educational content on NPD is presented and disseminated through the @anti.manipulasi Instagram account, and to examine users’ perceptions of such content. This research adopts a qualitative method using a virtual netnography approach. Data were collected through observation, interviews, and documentation. The findings show that the encoding process—how messages are crafted and shared—is carried out through structured content strategies, narrative and persuasive language, and the use of various Instagram features to distribute information about NPD. The content dissemination is considered an effective encoding process. Users’ perceptions of NPD content on @anti.manipulasi are overwhelmingly positive, appreciating it as accurate and helpful information. These audience responses reflect a dominant decoding position, in which users interpret the content in line with the intended message constructed by the content creator.